Pengaruh Motivasi Kerja, Disiplin Kerja, Dan Lingkungan Kerja Terhadap Kinerja Karyawan PT. PLN (Persero) ULP Gondanglegi - Ahmad Khoirul Anam; Budi Wahono; Fahrurrozi Rahman (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract The purpose of this study was to determine the effect of work motivation, work discipline and work environment on the performance of employees at PT PLN (Persero) ULP Gondanglegi. The type of research used is quantitative research. The sample used in this study amounted to 74 employee respondents with the technique used in the study, namely saturated sampling. The results showed that the results of the test f stated that work motivation, work discipline and work environment had a positive effect on performance togetge. Form the result of the t-test analysis, it can be concluded that all X variables have a partially significant effect on performance.  Keywords : Work Motivation, Work Discipline, Work Environment And Performance